2001
DOI: 10.1002/1096-9861(20010319)431:4<405::aid-cne1079>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic and sympathetic control of the pancreas: A role for the suprachiasmatic nucleus and other hypothalamic centers that are involved in the regulation of food intake

Abstract: To reveal brain regions and transmitter systems involved in control of pancreatic hormone secretion, specific vagal and sympathetic denervation were combined with injection of a retrograde transsynaptic tracer, pseudorabies virus (PRV), into the pancreas. After sympathetic or vagal transsection first-order neurons were revealed in the dorsal motor nucleus of the vagus (DMV) or in preganglionic spinal cord neurons (SPN), respectively. Careful timing of the survival of the animals allowed the detection of cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
205
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(218 citation statements)
references
References 79 publications
9
205
1
Order By: Relevance
“…Our finding of a circadian phase effect on early-phase insulin secretion could be mediated through the circadian system via numerous mechanisms. First, there are multisynaptic projections from the SCN to the pancreas (33,34). Second, pancreatic cells contain circadian clocks and their disruption, by knocking out circadian clock gene Brain and muscle Arnt-like protein-1 (BMAL1) specifically within the pancreas, results in decreased insulin secretion and impaired glucose tolerance (21,23).…”
Section: Discussionmentioning
confidence: 90%
“…Our finding of a circadian phase effect on early-phase insulin secretion could be mediated through the circadian system via numerous mechanisms. First, there are multisynaptic projections from the SCN to the pancreas (33,34). Second, pancreatic cells contain circadian clocks and their disruption, by knocking out circadian clock gene Brain and muscle Arnt-like protein-1 (BMAL1) specifically within the pancreas, results in decreased insulin secretion and impaired glucose tolerance (21,23).…”
Section: Discussionmentioning
confidence: 90%
“…15 Neuropeptide Y-and proopiomelanocortinexpressing neurons in the arcuate nucleus affect glucose metabolism via their projections to (pre-autonomic) hypothalamic neurons that control the autonomic nervous input to various peripheral organs, such as the pancreas. 25 Thus, it could well be that alterations in the brain in rats on a freechoice HFHS diet are mediating the effects on glucose metabolism via the ANS.…”
Section: Discussionmentioning
confidence: 92%
“…The pancreas is innervated by the ANS and it has been shown that the hypothalamus may regulate this sensitivity via this ANS innervation. [25][26][27][28] The latter hypothesis is supported by our recent finding that centrally, neuropeptide Y and proopiomelanocortin mRNA expression in the arcuate nucleus were altered in HFHS-choice diet rats in such a direction that it promotes glucose intolerance and insulin resistance. 15 Neuropeptide Y-and proopiomelanocortinexpressing neurons in the arcuate nucleus affect glucose metabolism via their projections to (pre-autonomic) hypothalamic neurons that control the autonomic nervous input to various peripheral organs, such as the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bilateral VMN lesioning induces hyperinsulinemia (49,50) whereas electrical stimulation of the VMN suppresses glucose-induced insulin secretion (51). Further, the VMN is known to regulate autonomic outflow to the pancreas (52,53), and activation of islet sympathetic nerves during glycopenic stress (54) inhibits insulin secretion via a mechanism involving activation of α2-adrenoreceptors on the beta cell (47,48). However, the neurocircuitry that underlies inhibitory control of insulin secretion by the brain remains unknown.…”
Section: Discussionmentioning
confidence: 99%